Sensitivities of the runaway current in JET disruptions to massive gas injection and initial plasma current - Gustavsson, Christian (My University, 2024)
The Joint European Torus (JET) tokamak, located at the Culham Centre for Fusion Energy in the UK, has been a leader in magnetic confinement fusion (MCF) research for decades. As the world’s largest operational tokamak until 2023, JET has sig nificantly advanced the understanding and technology needed for controlled fusion energy, which aims to provide a clean, large-scale energy source by replicating the processes that power the Sun. A primary challenge in tokamak operation is man aging plasma disruptions, which can terminate plasma confinement and generate runaway electrons (REs). These high-energy electrons can damage reactor compo nents, thus studying REs is vital for the viability of fusion energy. As the fusion community progresses towards advanced reactors like ITER in France and SPARC in the USA, understanding and controlling REs becomes even more important. This study uses the Disruption Runaway Electron Analysis Model (DREAM) to investigate the conditions under which REs form during tokamak disruptions. The main objective of this thesis is to model the conditions for the existence of REs in JET massive gas injection (MGI) discharges, focusing on their dependence on magnetic field strength, initial plasma current, as well as the ratio of injected argon to deuterium. Furthermore, we are interested in how much current is carried by the REs after a disruption. The analysis is conducted through a series of parameter scans using the simulation tool DREAM. Our simulation results show that the RE current is influenced by the initial plasma current and the ratio of injected argon to deuterium, with only a very weak dependence on magnetic field strength. More over, our findings suggest that the injection profile of argon significantly affects the parametric trends of the maximum RE current. A uniform injection profile yields an inverted current trend compared to an edge-peaked injection profile, where the latter yields results that are more in line with experimental results.
Keywords: : fusion plasma, runaway electron, massive material injection, massive gas injection, disruption mitigation, JET